Cyto‐morphologic spectrum of thyroid lesions in children. Issue 7 (6th April 2018) - Pathak, Priya; Sharma, Pooja; Daga, Aditi; Sharma, Sonal
Abstract : Introduction: Fine needle aspiration (FNA) is routinely used in triaging thyroid lesions in adults. However, role of FNA in pediatric thyroid lesions is less studied. Aim and objective: To study the cyto‐morphologic spectrum of thyroid lesions in pediatric population. Materials and methods: A retrospective analysis (duration‐6 years) of thyroid FNA for patients who were 18 years or younger was conducted. The aspirates were classified according to the Bethesda System for Reporting Cytopathology. Results: A total of 2716 thyroid aspirates were reviewed, out of which 327 (12%) were pediatric thyroid FNAs performed on 301 patients. Of these 256 (85%) were females and 45 (15%) were male patients. Aspirates were classified as follows: Nondiagnostic—30 (10%), Benign—260 (86%), Atypia of undetermined significance—6 (2%), Suspicious of follicular neoplasm—0 (0%), Suspicious of malignancy—0 (0%), Malignant—5 (2%). Out of the 253 benign lesions, 153 (58%) were spectrum of colloid goitre, 106 (42%) were Lymphocytic thyroiditis and 1(0.5%) was granulomatous thyroiditis (0.5%). Conclusion: Thyroid disorders are fairly common in children. Majority of these are benign in nature of which most common are spectrum of colloid goitre. With the benefits of being a noninvasive procedure and cost effective, FNA is a reliable method for screening and diagnosis of thyroid lesions in pediatric population.